Ancillary services markets in europe: Evolution and regulatory trade-offs. (February 2022) - Rancilio, G.; Rossi, A.; Falabretti, D.; Galliani, A.; Merlo, M.
Abstract: The generating power mix has deeply changed in the last years. Especially in Europe, the electric systems are evolving towards a more decentralized architecture, widely penetrated by renewable and distributed energy resources. These resources usually present less predictability and fast dynamics. To avoid jeopardizing the power system, they should be effectively included in the Ancillary Services Markets (ASMs), which procure the resources for balancing and safely dispatching the system. This work presents a meta-analysis of the evolution of ASMs and the underlying regulatory trade-offs. The evolutions are analyzed modularly to clearly investigate the benefit of each one. The analysis aims to provide an evaluation of each trend regarding the architecture, the services, and the products of the ASMs, based on the level of agreement of the two main counterparties: the system operator who manages the system and the Balancing Services Provider that delivers the service. The outcome is a ranking of the possible regulatory evolutions, with the win–win situations at the top and the cases that imply drawbacks for a counterparty at the bottom. The ranking can represent a guideline for regulatory authorities as well as market operators or players to realize effective market arrangements. Finally, a survey of European countries describes the effort of each one towards each evolution. Highlights: Ancillary services markets are evolving in Europe to integrate RESs and DERs. Asymmetric procurement or reserves is the main win–win evolution. Going towards marginal price and harmonizing the products can be beneficial as well. Central vs. self-dispatch system: an ongoing debate entailing many trade-offs.